2022
DOI: 10.1044/2022_aja-21-00123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Place-Based Versus Default Mapping Procedures on Masked Speech Recognition: Simulations of Cochlear Implant Alone and Electric-Acoustic Stimulation

Abstract: Purpose: Cochlear implant (CI) recipients demonstrate variable speech recognition when listening with a CI-alone or electric-acoustic stimulation (EAS) device, which may be due in part to electric frequency-to-place mismatches created by the default mapping procedures. Performance may be improved if the filter frequencies are aligned with the cochlear place frequencies, known as place-based mapping. Performance with default maps versus an experimental place-based map was compared for participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…[3][4][5] Additionally, specific mapping of individual electrodes along the cochlear axis offers the potential for use of novel programming strategies to improve performance. 16,17 Moreover, the ability to accurately localize these electrodes postplacement can lead to potentially altered surgical methods to improve electrode placement for accurate scalar targeting. 7,11 However, the main limitation to accurate localization is artifact from the electrodes on standard postinsertion CT, and radiographs lack the level of detail necessary for localization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Additionally, specific mapping of individual electrodes along the cochlear axis offers the potential for use of novel programming strategies to improve performance. 16,17 Moreover, the ability to accurately localize these electrodes postplacement can lead to potentially altered surgical methods to improve electrode placement for accurate scalar targeting. 7,11 However, the main limitation to accurate localization is artifact from the electrodes on standard postinsertion CT, and radiographs lack the level of detail necessary for localization.…”
Section: Resultsmentioning
confidence: 99%
“…Transscalar migration of the electrode indicates clinically significant intracochlear trauma that results in loss of residual acoustic hearing and may also impact electrode‐only stimulation 3–5 . Additionally, specific mapping of individual electrodes along the cochlear axis offers the potential for use of novel programming strategies to improve performance 16,17 . Moreover, the ability to accurately localize these electrodes postplacement can lead to potentially altered surgical methods to improve electrode placement for accurate scalar targeting 7,11 .…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the last assessment the subject chose the fitting he/she preferred (CONSORT Flow Chart). Because the effect of frequency-to-place mismatch on speech recognition was observed at 1-month postactivation (Canfarotta et al 2020a,b,c) and the effect of place-based fitting was observed acutely (Dillon et al 2021a,b; Jiam et al 2019; Dillon et al 2022), the 6-week duration was a suitable compromise to ensure an acclimation period that is long enough to observe a significant effect (if it exits) and a bearable duration for the subjects in case of a significant difference between the two fitting methods. Participants and those assessing the outcomes were blinded to intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have suggested that insertion depth has an impact on speech perception in quiet or in noise (Buchman et al 2014; Hochmair et al 2015; O’Connell et al 2016, 2017; Canfarotta et al 2022) and that these results may be due to an improvement of the tonotopic alignment, that is, to a reduction of the frequency-to-place mismatch. However, increased frequency-to-place mismatch has been shown to negatively affect speech recognition in CI users and in simulations with normal-hearing listeners (Başkent & Shannon 2004; Canfarotta et al 2020a,b,c; Dillon et al 2021a, 2022; Dorman et al 1997; Fu & Shannon 1999a,b; Yukawa et al 2004; Li & Fu 2010; Mertens et al 2021). Adaptation to a spectral upshift up to three octaves has been observed (Reiss et al 2007), but studies have shown it could remain incomplete even after extensive training and years of experience (Svirsky et al 2004; Sagi et al 2010; Reiss et al 2014; Dorman et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The default mapping procedures for cochlear implant (CI) alone and electric-acoustic stimulation (EAS) devices do not incorporate the individual variability in anatomy or electrode array placement relative to the cochlear tonotopicity, resulting in discrepancies between the electric filter frequencies and cochlear place frequencies, 1,2 known as electric frequency-to-place mismatches. Listeners of CI-alone and EAS simulations and CI-alone users experience poorer speech recognition when listening to maps with frequency-to-place mismatches as compared to maps with the filter frequencies matched to the cochlear place frequencies, [3][4][5][6][7][8][9][10][11][12][13][14][15] referred to here as placebased maps. Place-based mapping procedures incorporate the individual variability in electrode array placement relative to the cochlear tonotopicity in the assignment of the electric filter frequencies for individual electrode contacts to eliminate frequency-to-place mismatches.…”
Section: Introductionmentioning
confidence: 99%